Environmental Impacts of Aquaculture in the Philippines - Tahiluddin, Albaris B.; Bornales, Jonald C.; Limbaro, Gindol Rey A.; Paudac, Mohammad Al-Thanie U.; Amarille, Randell Keith; Sirad, Naima R.; Kabirun, Mariam C.; Ujing, Romar A.; Gonzaga-Torino, Floriefe M.; Sabdani, Mardiya H.; Bacla-an, Ramonito E.; Hairal, Moh. Abdul-jan S.; et al. (SAABRON PRESS, 2025)
Aquaculture is one of the fastest-growing industries globally, hailed as a crucial source of aquatic food for human consumption. In the Philippines, a nation with a significant stake in global aquaculture, this sector not only supports food security and provides livelihoods but also boosts the national economy by generating valuable export revenue. However, the rapid expansion of aquaculture in the country has sparked concerns, particularly regarding its environmental footprint. This work critically reviews the environmental impacts of aquaculture in the Philippines by reviewing available literature published from 1918 up to the present on the environmental impacts of Philippine aquaculture using relevant keywords from databases like Scopus, Web of Science, PubMed, Google Scholar, and ResearchGate, and some Philippine government databases like the Philippine Statistics Authority and Bureau of Fisheries and Aquatic Resources. While aquaculture plays a key role in ensuring food security, sustaining livelihoods, and supporting the country’s economic growth, it has also been linked to several environmental issues. These include the destruction of mangrove habitats, degradation of seagrass ecosystems, sediment disruption, water pollution, and declining water quality. Moreover, the presence of antibiotic-resistant genes and residues in farmed species, alongside the introduction of non-native species, has triggered biodiversity imbalances and ecosystem degradation. This review underscores the urgent need for mitigation strategies to address these environmental impacts and proposes actionable solutions. Looking ahead, the future of Philippine aquaculture will depend on how well it balances growth with sustainability, ensuring the sector’s continued contribution to the economy and the environment.